Characterization of Citrus tristeza virus and determination of genetic variability in North-east and South India - and KAJAL K. BISWAS*, AVIJIT TARAFDAR, SHRUTI GODARA, SUMITA DWIVEDI, B.K. JAYAKUMAR (Indian Phytopathology, 2013)
Citrus tristeza virus (CTV) is an important plant virus under genus Closterovirus causing huge losses of citrus trees in India. Assam and Meghalaya states in the Northeast and Tirupati region in Andhra Pradesh in the South of India produce many commercial citrus fruits. A survey was made in citrus growing areas in these two regions to study the incidence of CTV disease and several infected citrus samples were collected for detection and molecular characterization of the virus. Twenty two CTV isolates; 11 from Tirupati, seven from Assam and four from Meghalaya were characterized and genetic diversity among them were determined based on sequencing of a 404 nt fragment of L Pro domain of 5’ORF1a (5’ORF1a) and complete CP gene (672 nt) of CTV genome. Pair-wise sequence analyses showed a range of 83-98% and 88-99% nt identity among the Assam-Meghalaya; and 88-98% and 87-98% nt identity among the Tirupati isolates, for 5’ORF1a and CP gene, respectively. Phylogenetic analyses determined that Assam-Meghalaya isolates fell into four to five and the Tirupati isolates into three to five genogroups based on 5’ORF1a and CP gene. The recombination-detecting program RDP3 identified recombination events in the isolates MB3, MB6 and MU6 of Meghalaya, and AR1 and TP6 of Tirupati and determined them as putative recombinant isolates originating by exchange of genetic material from diverse CTV isolates.